Electrolyte additive composition, electrolyte and battery
By using electrolyte additive compositions with specific structural functional additives and lithium salt additives in lithium-ion batteries, the problem of the increase in the acidity of the electrolyte in high-voltage lithium-ion batteries under high temperature conditions is solved, and the circulation and storage performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202411963776.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The electrolyte acidity of high-voltage lithium-ion battery system increases under high temperature conditions, resulting in deterioration of electrochemical performance.
An electrolyte additive composition is provided, including lithium salt additives and functional additives. The structural formula of the functional additives is specific, which can promote the formation of SEI films and CEI films, reduce the acidity of the electrolyte, and remain stable at high voltages.
By improving the stability of the electrolyte and the formation of the membrane, the circulation performance and storage performance of the high-voltage battery system under high temperature conditions are significantly improved, and the cycle life of the battery is extended.
Smart Images

Figure CN119764569A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to an electrolyte additive composition, an electrolyte and a battery. Background Art
[0002] With the development of portable electronic devices, electric vehicles and hybrid vehicles, consumers have higher and higher requirements for the energy density, power density and cycle life of batteries. High operating voltage is one of the ways to improve the energy density of lithium-ion batteries, but under high voltage, especially when circulating or storing under high temperature conditions, the water content and HF (hydrofluoric acid) in the electrolyte will increase, resulting in an increase in the acidity of the electrolyte. Among them, HF and H2O will destroy the SEI (solid electrolyte interface) film and CEI (positive electrode electrolyte interface) film formed on the electrode surface, resulting in a decrease in cycle performance, while HF in an acidic environment will corrode the electrode material and intensify the side reactions inside the battery, resulting in a decrease in the capacity retention rate of the battery during circulation or storage and a shortened cycle life. Summary of the invention
[0003] The main purpose of the present application is to provide an electrolyte additive composition, an electrolyte and a battery to solve the problem of increased electrolyte acidity and deterioration of electrochemical performance of high-voltage battery systems under high temperature conditions in the related art.
[0004] In order to achieve the above object, according to the first aspect of the present application, an electrolyte additive composition is provided, the electrolyte additive composition comprising a lithium salt additive and a functional additive, the structural formula of the functional additive is shown in Formula 1:
[0005]
[0006] Further, the mass ratio of the lithium salt additive to the functional additive is (0.5-1): (0.3-1);
[0007] Preferably, the lithium salt additive includes at least one of lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, lithium bis(oxalatoborate), and lithium difluorobis(oxalatophosphate).
[0008] Furthermore, the electrolyte additive composition further includes a carbonate additive; the mass ratio of the carbonate additive to the functional additive is (0.2-1): (0.3-1);
[0009] Preferably, the carbonate additive includes vinylene carbonate and / or fluoroethylene carbonate;
[0010] Furthermore, the electrolyte additive composition also includes a sulfur-containing additive; the mass ratio of the sulfur-containing additive to the functional additive is (0.5-2): (0.3-1);
[0011] Preferably, the sulfur-containing additive includes at least one of propylene sulfite, 1,3-propane sultone, and ethylene sulfite.
[0012] According to a second aspect of the present application, there is provided an electrolyte, which includes a lithium salt, an organic solvent, and the electrolyte additive composition provided in the first aspect.
[0013] Furthermore, the mass fraction of the lithium salt in the electrolyte is 9.5% - 15%; and / or,
[0014] the mass fraction of the organic solvent in the electrolyte is 80% - 90%; and / or,
[0015] the mass fraction of the electrolyte additive composition in the electrolyte is 0.5% - 5%.
[0016] Furthermore, the mass fraction of the functional additive in the electrolyte is 0.3% - 1%; and / or,
[0017] the mass fraction of the lithium salt additive in the electrolyte is 0.5% - 1%; and / or,
[0018] the mass fraction of the carbonate additive in the electrolyte is 0.2 - 1%; and / or,
[0019] the mass fraction of the sulfur-containing additive in the electrolyte is 0.5% - 2%.
[0020] Furthermore, the organic solvent includes at least two of ethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate;
[0021] Preferably, the organic solvent includes ethylene carbonate and ethyl methyl carbonate;
[0022] More preferably, the organic solvent further includes at least one of dimethyl carbonate and diethyl carbonate.
[0023] According to a third aspect of the present application, there is provided a battery, which includes the electrolyte provided in the second aspect.
[0024] Furthermore, the battery further includes a negative electrode sheet containing a negative electrode active material; and / or,
[0025] the battery further includes a positive electrode sheet containing a positive electrode active material;
[0026] Preferably, the negative electrode active material includes a carbon-based negative electrode material; the positive electrode active material includes a nickel cobalt manganese ternary material, and the chemical formula of the nickel cobalt manganese ternary material is Li(Ni x Co y Mn z )O2, where 0.5 ≤ x < 0.8, 0 < y ≤ 0.3, 0 < z ≤ 0.3 and x + y + z = 1.
[0027] By applying the technical solution of the present application, the electrolyte additive composition of the present application is applied to a battery. On the one hand, the electrolyte additive has good reactivity, can effectively promote the formation of CEI film and SEI film, separate the electrolyte from the electrode, reduce the side reactions of the electrolyte, and improve the cycle performance of the battery; on the other hand, the functional additive contains N with a lone pair of electrons in the structural formula, which can effectively eliminate HF and H2O in the electrolyte, inhibit the increase in the acidity of the electrolyte, and improve the stability of the electrolyte. In addition, the functional additive has strong oxidation stability, which makes it difficult to decompose under high voltage, enhances the high voltage resistance of the electrolyte, thereby effectively improving the high temperature cycle performance and high temperature storage performance of the battery under high voltage, and extending the cycle life of the battery. DETAILED DESCRIPTION
[0028] As described in the background of this application, the existing high-voltage battery system has the problem of increased electrolyte acidity and deteriorated electrochemical performance under high temperature conditions. In order to solve the above problems, the first aspect of this application provides an electrolyte additive composition, including a lithium salt additive and a functional additive, the structural formula of the functional additive is shown in Formula 1:
[0029]
[0030] First, the structural formula of the functional additive contains a C=C bond, which can participate in the formation of the CEI film and the SEI film on the surface of the positive and negative electrodes. The formation of a stable CEI film and SEI film can effectively separate the electrolyte from the electrode and reduce the occurrence of side reactions of the electrolyte. Secondly, the structural formula of the functional additive contains a benzene ring and a fluorine atom (F) on the benzene ring. The high electronegativity and strong CF bond of the fluorine atom can improve the oxidative stability of the molecule, making the functional additive difficult to decompose under high voltage, thereby enhancing the high-voltage resistance of the electrolyte. In addition, the structural formula of the functional additive contains nitrogen-containing groups, such as carbon-nitrogen bonds and dimethylamino groups, wherein dimethylamino refers to a nitrogen atom (N) connected to two methyl groups (CH3) by a single bond. These nitrogen-containing groups have a certain alkalinity and can react with acidic substances in the electrolyte, such as HF, to reduce the acidity of the electrolyte, improve the stability of the electrolyte, and take into account the improvement of the normal temperature cycle performance, high temperature cycle performance and high temperature storage performance of the battery under high voltage.
[0031] Lithium salt additives and functional additives can jointly participate in the formation of SEI film and CEI film. The joint action of functional additives and lithium salt additives can promote the stability and density of the film. In addition, lithium salt additives also have high oxidation stability, can participate in electrochemical reactions, can maintain the stability of the electrolyte under high voltage, and reduce the decomposition of the electrolyte. The synergistic effect of lithium salt additives and functional additives can significantly improve the stability of the electrolyte under high voltage conditions.
[0032] In summary, by introducing functional additives with specific structural formulas, under the joint action of functional additives and lithium salt additives, the reaction activity, oxidation stability and chemical stability of the additives can be improved, the acidity of the electrolyte can be effectively inhibited, side reactions can be reduced, and electrode materials can be protected. The cycle performance and storage performance of the high-voltage battery system under high temperature conditions can be significantly improved, thereby achieving long-term stability and efficient operation of the battery system.
[0033] In some embodiments, the mass ratio of the lithium salt additive to the functional additive is (0.5-1): (0.3-1), such as 0.5:1, 0.8:1, 1:1, 0.8:0.5, 0.8:0.3, 0.5:0.3 or any two of them. By limiting the mass ratio of the lithium salt additive to the functional additive, the stability of the electrolyte can be further improved, the formation of the SEI film / CEI film can be optimized, the performance of the high voltage battery system at high temperature can be improved, and the battery cycle life can be extended.
[0034] The present application does not limit the specific type of lithium salt additive, which can be a conventional lithium salt additive in the art. For example, in some preferred embodiments, the lithium salt additive includes at least one of lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorophosphate (LiPO2F2), lithium bis(oxalatoborate) (LiBOB), and lithium difluorobis(oxalatophosphate) (LiODFP).
[0035] In some embodiments, the electrolyte additive composition also includes a carbonate additive; the mass ratio of the carbonate additive to the functional additive is (0.2-1):(0.3-1), for example, 0.2:1, 0.5:1, 0.8:1, 1:1, 1:0.8, 1:0.5, 1:0.3 or a range consisting of any two of them.
[0036] During the first charge of lithium-ion batteries, carbonate additives can preferentially decompose on the electrode surface, participate in the formation of SEI film and CEI film, reduce internal side reactions, and thus control the gas production and expansion of the battery during high-temperature storage or cycling. At the same time, carbonate solvents have high thermal stability and can maintain the physical and chemical properties of the electrolyte at high temperatures. By adding carbonate solvents, the overall thermal stability of the electrolyte can be enhanced and the possibility of electrolyte decomposition at high temperatures can be reduced. Therefore, by introducing carbonate additives, the composition of the electrolyte is optimized under the joint action of lithium salt additives, functional additives and carbonate additives, thereby further improving the high-temperature storage performance of the battery, extending the battery life, and improving the safety and reliability of the battery.
[0037] By limiting the mass ratio of carbonate additives to functional additives to (0.2-1): (0.3-1), the physicochemical properties of the entire electrolyte, including viscosity, conductivity, and chemical stability, can be optimized, thereby improving the overall performance of the battery.
[0038] The present application does not limit the specific type of carbonate additives, and the carbonate additives may be conventional carbonate additives in the art. For example, in some embodiments, the carbonate additives include vinylene carbonate and / or fluoroethylene carbonate.
[0039] In some embodiments, the electrolyte additive composition further includes a sulfur-containing additive; the mass ratio of the sulfur-containing additive to the functional additive is (0.5-2): (0.3-1).
[0040] During the battery cycle, sulfur-containing additives can promote the formation of more stable and dense SEI and CEI films on the electrode surface. These two layers of membranes can effectively isolate the electrode material from the electrolyte, reduce side reactions, and thus improve the battery's cycle efficiency and service life. At the same time, sulfur-containing additives can improve the electrolyte's antioxidant properties, allowing the battery to maintain stable cycle performance at high voltages, help reduce the battery's performance decay rate under high-temperature storage conditions, reduce gas generation inside the battery, reduce battery expansion, and improve the battery's capacity retention rate after long-term high-temperature storage. In addition, sulfur-containing compounds have high thermal stability and can enhance the thermal stability of the electrolyte system, allowing the battery to maintain good electrochemical properties in a high-temperature environment, reduce electrolyte decomposition, and inhibit the generation of harmful substances (such as water and hydrofluoric acid).
[0041] The mass ratio of the sulfur-containing additive to the functional additive is (0.5-2): (0.3-1), for example, it can be 0.5:1, 0.8:1, 1:1, 2:1, 2:0.5, 2:0.3 or any two of them. By limiting the mass ratio of the sulfur-containing additive to the functional additive within the above range, the SEI / CEI film formation inside the battery can be optimized through synergistic effects, and the cycle performance and storage performance of the battery under high temperature conditions can be further improved.
[0042] The present application does not limit the specific type of sulfur-containing additive, and it can be a conventional sulfur-containing additive in the art. For example, in some embodiments, the sulfur-containing additive includes at least one of propylene sulfite (PS), 1,3-propane sultone (PST), and ethylene sulfate (DTD).
[0043] In a second aspect of the present application, an electrolyte is provided, the electrolyte comprising a lithium salt, an organic solvent and the electrolyte additive composition provided in the first aspect.
[0044] The electrolyte additive composition can not only improve the cycle performance of the battery under high temperature conditions, but also help reduce the performance decay rate of the battery under high temperature storage conditions, reduce gas generation inside the battery, reduce battery expansion, and improve the capacity retention rate of the battery after long-term high temperature storage.
[0045] Lithium salt is the main source of conductive ions in the electrolyte. In some embodiments, the mass fraction of lithium salt in the electrolyte is 9.5% to 15%. By limiting the amount of lithium salt added within the above range, it is possible to ensure that the electrolyte has sufficient conductivity, ensure efficient ion transmission during the charge and discharge process of the battery, and at the same time, ensure that there is enough lithium salt to participate in the formation of the SEI / CEI film.
[0046] The mass fraction of the lithium salt in the electrolyte is 9.5% to 15%, for example, 9.5%, 10%, 11%, 12%, 13%, 14%, 15% or a range consisting of any two thereof.
[0047] In some embodiments, the mass fraction of the electrolyte additive composition in the electrolyte is 0.5% to 5%. By limiting the addition amount of the electrolyte additive composition to the above range, it is ensured that the electrolyte additive composition can play an effective role in the electrolyte to the maximum extent.
[0048] The mass fraction of the electrolyte additive composition in the electrolyte is 0.5% to 5%, for example, 0.5%, 1%, 2%, 3%, 4%, 5% or any two thereof.
[0049] Organic solvent is the main component of the electrolyte and is responsible for transporting lithium ions. In some embodiments, the mass fraction of organic solvent in the electrolyte is 80% to 90%. By limiting the amount of organic solvent added within the above range, sufficient fluidity can be provided to ensure the rapid transmission of lithium ions between electrodes, thereby maintaining the high conductivity of the battery; secondly, the appropriate solvent ratio is conducive to the formation of a stable and dense interface film, promotes the formation of SEI / CEI film, and reduces side reactions; in addition, it also helps to ensure that the electrolyte has suitable viscosity, conductivity and chemical stability, and can maintain stable lithium ion transmission even under high temperature conditions, thereby improving the high temperature cycle performance and high temperature storage performance of lithium-ion batteries.
[0050] The mass fraction of the organic solvent in the electrolyte is 80% to 90%, for example, 80%, 82%, 84%, 86%, 88%, 90% or a range consisting of any two thereof.
[0051] Through the synergistic effect of lithium salt, electrolyte additive composition and organic solvent, the viscosity and conductivity of the electrolyte can be optimized to maintain good stability, thereby improving the cycle performance and storage performance of the battery under high temperature conditions.
[0052] This application does not limit the proportion of each additive in the electrolyte, as long as the above requirements are met. For example, in some embodiments, the mass fraction of the functional additive in the electrolyte is 0.3% to 1%. By limiting the amount of functional additives added, it can not only play its role in improving high-temperature cycle performance and high-temperature storage performance, but also avoid changes in electrolyte viscosity or increased costs, which helps to achieve electrolyte formulation optimization and lithium-ion battery performance improvement.
[0053] In some embodiments, the mass fraction of the functional additive in the electrolyte is 0.3% to 1%, such as 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or any two of them. By limiting the amount of functional additives added, the role of the functional additives can be maximized, effectively improving the cycle performance and storage performance of the battery under high pressure and high temperature, and achieving electrolyte formulation optimization and battery electrochemical performance improvement.
[0054] In some embodiments, the mass fraction of the lithium salt additive in the electrolyte is 0.5% to 1%, such as 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or any two thereof. The lithium salt additive can participate in the electrochemical reaction. By limiting the amount of the lithium salt additive, in addition to maintaining the high temperature cycle performance and high temperature storage performance of the battery, the energy density of the battery can also be improved.
[0055] In some embodiments, the mass fraction of carbonate additives in the electrolyte is 0.2-1%, such as 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or any two of them. By limiting the amount of carbonate additives added, the formation of a uniform and dense SEI film can be promoted to maximize its multiple functions.
[0056] In some embodiments, the mass fraction of the sulfur-containing additive in the electrolyte is 0.5% to 3%, such as 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, or any two thereof. By limiting the amount of sulfur-containing additive added, the effectiveness of the additive can be ensured while taking into account the cost.
[0057] The present application does not limit the specific type of organic solvent, which can be a conventional organic solvent in the art. In some embodiments, the organic solvent includes at least two of ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). In this way, the advantages of carbonate solvents can be combined to improve the overall performance of the battery.
[0058] In some embodiments, the organic solvent includes ethylene carbonate and ethyl methyl carbonate; further, the organic solvent also includes at least one of dimethyl carbonate and diethyl carbonate. By finely adjusting the volume ratio of ethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate, the cycle performance, high and low temperature adaptability, safety, and stability of the electrolyte of the high voltage lithium ion battery can be significantly improved, thereby improving the overall performance and service life of the battery.
[0059] The present application does not limit the specific preparation method of the electrolyte, as long as it contains the above components. For example, the specific preparation method of the electrolyte includes the following steps: adding the electrolyte additive composition to the organic solvent under a protective atmosphere, then adding the lithium salt, stirring and mixing at a first temperature to obtain the electrolyte; wherein the protective atmosphere can be argon gas, and the first temperature can be 5 to 15°C.
[0060] A third aspect of the present application provides a battery, comprising the electrolyte provided in the second aspect.
[0061] Due to the inclusion of the above electrolyte, the battery has excellent high-temperature cycle performance and high-temperature storage performance. Specifically, the gas generation is reduced during charge and discharge cycles under high voltage and high temperature conditions, the HF content is reduced, the capacity retention rate is high after long-cycle cycles, and the capacity loss and volume expansion are low during high-temperature storage.
[0062] In some embodiments, the battery further includes a negative electrode sheet containing a negative electrode active material and a positive electrode sheet containing a positive electrode active material.
[0063] The negative electrode sheet includes a negative electrode current collector and a negative electrode active layer formed of a negative electrode active material and disposed on the surface of the negative electrode current collector.
[0064] When preparing the negative electrode sheet, the negative electrode active material, the first conductive agent, and the first binder can be dispersed in an appropriate amount of solvent, and fully stirred and mixed to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector, and the negative electrode sheet is obtained after drying, rolling and cutting. In a specific embodiment, the negative electrode active layer includes 70% to 99% of graphite negative electrode material, 0.5% to 15% of conductive agent, and 0.5% to 15% of binder in terms of mass percentage.
[0065] Among them, the material of the negative electrode current collector can be at least one of copper foil, nickel foam, and copper foam; the first conductive agent can be selected from at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, and graphene; the first binder can be selected from at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyvinyl alcohol, and sodium polyacrylate.
[0066] The present application does not limit the specific type of the negative electrode active material in the negative electrode sheet, which can be the negative electrode active material commonly used in current batteries. In some embodiments, the negative electrode active material includes a carbon-based negative electrode material, such as at least one of graphite, hard carbon, soft carbon, and mesophase carbon microspheres.
[0067] The positive electrode sheet includes a positive electrode current collector and a positive electrode active layer formed of a positive electrode active material provided on the surface of the positive electrode current collector.
[0068] When specifically preparing the positive electrode sheet, the positive electrode active material, a second conductive agent, and a second binder can be dispersed in an appropriate amount of solvent, and sufficiently stirred and mixed to form a uniform positive electrode paste; the positive electrode paste is uniformly coated on the positive electrode current collector, and after drying, rolling, and slitting, the positive electrode sheet is obtained. In a specific embodiment, the positive electrode active layer includes 70% to 99% of the positive electrode active material, 0.5% to 15% of the conductive agent, and 0.5% to 15% of the binder by mass percentage.
[0069] Among them, the material of the positive electrode current collector can be at least one of aluminum foil and nickel foil; the second conductive agent can be selected from at least one of carbon black, acetylene black, graphene, Ketjen black, and carbon fiber; the second binder can be selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polyethylene, polypropylene, polyvinyl alcohol, and sodium polyacrylate.
[0070] The present application does not limit the specific type of the positive electrode active material in the positive electrode sheet, which can be the positive electrode active material commonly used in current batteries, such as at least one composite oxide of lithium and at least one metal of cobalt, nickel, manganese, and their combinations. Specifically, the positive electrode active material can be a nickel cobalt manganese ternary material, and the chemical formula of the nickel cobalt manganese ternary material is Li(Ni x Co y Mn z )O2, where 0.5 ≤ x < 0.8, 0 < y ≤ 0.3, 0 < z ≤ 0.3 and x + y + z = 1.
[0071] The battery further includes a separator. The present application does not limit the specific selection of the separator material, which can be the separator material commonly used in current batteries, such as a polypropylene separator, a polyethylene separator, a polypropylene / polyethylene double-layer composite separator, a polypropylene / polyethylene / polypropylene (PP / PE / PP) three-layer composite separator, etc.
[0072] When preparing the battery, the positive electrode sheet, the separator, and the negative electrode sheet are wound or laminated to obtain an electrode core, the electrode core is encapsulated into a pre-stamped aluminum plastic film, after the encapsulated battery is dried to remove moisture, the electrolyte is injected into the dried battery, and the battery is completed after aging, formation, and secondary sealing.
[0073] The present application is further described in detail below in conjunction with specific examples, which should not be construed as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0074] Example 1
[0075] The electrolyte of this embodiment is composed of an organic solvent, a lithium salt and an additive; the additive includes fluoroethylene carbonate (FEC), lithium difluorophosphate (LiPO2F2), 1,3-propane sultone and a functional additive as shown in Formula 1, and the CAS number is 138716-60-6;
[0076] Among them, the mass fraction of fluoroethylene carbonate in the electrolyte is 0.5%, the mass fraction of lithium difluorophosphate in the electrolyte is 0.5%, the mass fraction of 1,3-propane sultone in the electrolyte is 1%, and the mass fraction of functional additives in the electrolyte is 0.3%;
[0077]
[0078] The lithium salt is lithium hexafluorophosphate, and its concentration in the electrolyte is 1.0 mol / L, and its mass fraction in the electrolyte is 12.5%; the mass fraction of the organic solvent in the electrolyte is 85.2%, and the organic solvent is composed of ethylene carbonate, diethyl carbonate, and ethyl methyl carbonate. Taking the total volume of the organic solvent as 100%, the volume fraction of ethylene carbonate is 30%, the volume fraction of diethyl carbonate is 20%, and the volume fraction of ethyl methyl carbonate is 50%.
[0079] The preparation method of the electrolyte of this embodiment includes: under an argon atmosphere, according to the above mass fractions, adding a formula amount of vinylene carbonate, lithium difluorophosphate, 1,3-propane sultone and functional additives to an organic solvent, then adding lithium hexafluorophosphate, stirring and mixing at a temperature of 10°C to obtain an electrolyte.
[0080] Example 2
[0081] The difference from Example 1 is that the mass fraction of the functional additive in the electrolyte is 0.5%, the total mass fraction is reduced to 100% by using an organic solvent, and the contents of other components are the same as in Example 1.
[0082] Example 3
[0083] The difference from Example 1 is that the mass fraction of the functional additive in the electrolyte is 1%, the total mass fraction is reduced to 100% by using an organic solvent, and the contents of other components are the same as in Example 1.
[0084] Example 4
[0085] The difference from Example 1 is that the mass fraction of the functional additive in the electrolyte is 2%, the total mass fraction is reduced to 100% by using an organic solvent, and the contents of other components are the same as in Example 1.
[0086] Example 5
[0087] The difference from Example 1 is that the mass fraction of lithium difluorophosphate in the electrolyte is 0.8%, the total mass fraction is reduced to 100% by using an organic solvent, and the contents of other components are the same as in Example 1.
[0088] Example 6
[0089] The difference from Example 1 is that the mass fraction of lithium difluorophosphate in the electrolyte is 1%, the total mass fraction is reduced to 100% by using an organic solvent, and the contents of other components are the same as in Example 1.
[0090] Example 7
[0091] The difference from Example 1 is that the mass fraction of lithium difluorophosphate in the electrolyte is 2%, the total mass fraction is reduced to 100% by using an organic solvent, and the contents of other components are the same as in Example 1.
[0092] Example 8
[0093] The difference from Example 1 is that the mass fraction of fluoroethylene carbonate in the electrolyte is 0.2%, the total mass fraction is increased to 100% by using an organic solvent, and the contents of other components are the same as in Example 1.
[0094] Example 9
[0095] The difference from Example 1 is that the mass fraction of fluoroethylene carbonate in the electrolyte is 1%, the total mass fraction is reduced to 100% by using an organic solvent, and the contents of other components are the same as in Example 1.
[0096] Example 10
[0097] The difference from Example 1 is that the mass fraction of fluoroethylene carbonate in the electrolyte is 2%, and the total mass fraction is reduced to 100% by using an organic solvent. The contents of other components are the same as in Example 1.
[0098] Embodiment 11
[0099] The difference from Example 1 is that the mass fraction of 1,3-propane sultone in the electrolyte is 0.5%, the total mass fraction is increased to 100% by using an organic solvent, and the contents of other components are the same as in Example 1.
[0100] Example 12
[0101] The difference from Example 1 is that the mass fraction of 1,3-propane sultone in the electrolyte is 2%, the total mass fraction is reduced to 100% by using an organic solvent, and the contents of other components are the same as in Example 1.
[0102] Embodiment 13
[0103] The difference from Example 1 is that the mass fraction of 1,3-propane sultone in the electrolyte is 3%, the total mass fraction is reduced to 100% by using an organic solvent, and the contents of other components are the same as in Example 1.
[0104] Embodiment 14
[0105] The difference from Example 1 is that fluoroethylene carbonate is not added, the total mass fraction is increased to 100% by using an organic solvent, and the contents of other components are the same as in Example 1.
[0106] Embodiment 15
[0107] The difference from Example 1 is that 1,3-propane sultone is not added, the total mass fraction is increased to 100% by using an organic solvent, and the contents of other components are the same as in Example 1.
[0108] Example 16
[0109] The difference with Example 1 is that the organic solvent consists of ethylene carbonate, diethyl carbonate and ethyl methyl carbonate, and based on the total volume of the organic solvent as 100%, the volume fraction of ethylene carbonate is 40%, the volume fraction of diethyl carbonate is 10%, and the volume fraction of ethyl methyl carbonate is 50%.
[0110] Embodiment 17
[0111] The difference with Example 1 is that the organic solvent consists of ethylene carbonate, diethyl carbonate and ethyl methyl carbonate, and based on the total volume of the organic solvent as 100%, the volume fraction of ethylene carbonate is 10%, the volume fraction of diethyl carbonate is 70%, and the volume fraction of ethyl methyl carbonate is 20%.
[0112] Comparative Example 1
[0113] The difference from Example 1 is that no functional additive is added, the total mass fraction is increased to 100% by using an organic solvent, and the contents of other components are the same as in Example 1.
[0114] Comparative Example 2
[0115] The difference from Example 1 is that lithium difluorophosphate is not added, the total mass fraction is increased to 100% by using an organic solvent, and the contents of other components are the same as in Example 1.
[0116] Comparative Example 3
[0117] The difference from Example 1 is that the functional additive is replaced by an additive as shown in Formula 2:
[0118]
[0119] Comparative Example 4
[0120] The difference from Example 1 is that the functional additive is replaced by an additive as shown in Formula 3:
[0121]
[0122] Comparative Example 5
[0123] The difference from Example 1 is that the functional additive is replaced by an additive as shown in Formula 4:
[0124]
[0125] Comparative Example 6
[0126] The difference from Example 1 is that the functional additive is replaced by an additive as shown in Formula 5:
[0127]
[0128] Test example
[0129] The electrolytes of the embodiment and the comparative example were applied to lithium-ion batteries, and the performance of the lithium-ion batteries was tested. The specific preparation method of the lithium-ion battery includes: mixing graphite, acetylene black, carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 94:1:2:3 to form a negative electrode slurry; coating the negative electrode slurry on a copper foil current collector, vacuum drying, and preparing a negative electrode sheet;
[0130] The positive electrode material Li(Ni 0.5 Co 0.2 Mn 0.3 )O2, acetylene black and polyvinylidene fluoride are mixed in a mass ratio of 94:3:3 to form a positive electrode slurry; the positive electrode slurry is coated on an aluminum foil current collector, and vacuum dried to obtain a positive electrode sheet;
[0131] The positive electrode sheet, Celgard2400 separator and negative electrode sheet are wound or stacked to obtain a battery cell, and the battery cell is encapsulated in a pre-stamped aluminum-plastic film. After the encapsulated battery is dried to remove moisture, the electrolyte of the embodiment and the comparative example is injected into the dried battery. After the battery is aged, formed and sealed for a second time, a lithium ion battery is obtained.
[0132] The electrochemical test was carried out using the Xinwei charge and discharge test cabinet, and the HF content of the electrolyte was determined using the ice water titration method:
[0133] (1) Normal temperature cycle performance test:
[0134] At 25°C, the lithium-ion battery is charged at a constant current of 1.0C (nominal capacity) to a voltage of 4.4V, then charged at a constant voltage of 4.4V to a current ≤ 0.05C, left for 10 minutes, and then discharged at a constant current of 1C to a cut-off voltage of 2.8V. The above is one charge and discharge cycle. The lithium-ion battery is charged and discharged 1000 times under the above conditions.
[0135] Capacity retention rate (%) of a lithium-ion battery after 1000 cycles = (discharge capacity at the 1000th cycle / initial discharge capacity) × 100%.
[0136] (2) High temperature cycle performance test
[0137] At 45°C, the lithium-ion battery is charged at a constant current of 1.0C (nominal capacity) to a voltage of 4.4V, then charged at a constant voltage of 4.4V to a current ≤ 0.05C, left for 10 minutes, and then discharged at a constant current of 1C to a cut-off voltage of 2.8V. The above is one charge and discharge cycle. The lithium-ion battery is charged and discharged 1000 times under the above conditions.
[0138] Capacity retention rate (%) of a lithium-ion battery after 1000 cycles = (discharge capacity at the 1000th cycle / initial discharge capacity) × 100%.
[0139] (3) Electrolyte HF content test:
[0140] The electrolyte was stored at 45°C, and the HF contents at 0d and 15d were measured by ice water titration, respectively, and recorded as HF-0d and HF-15d.
[0141] (4) High temperature storage performance test of lithium-ion batteries:
[0142] At 25°C, the lithium-ion battery was charged at a constant current of 1C to a voltage of 4.4V, and then charged at a constant voltage of 4.4V to a current of 0.05C. The volume of the tested lithium-ion battery was V0, and the initial capacity was C0. The lithium-ion battery was then placed in a constant temperature box at 60°C and stored for 90 days, and the volume of the tested lithium-ion battery was taken out and recorded as V1, the capacity remained C1, and the capacity recovered to C2.
[0143] The volume expansion rate (%) of a lithium-ion battery after storage at 60°C for 90 days = (V1-V0) / V0×100%.
[0144] The capacity retention rate (%) of the lithium-ion battery after storage at 60° C. for 90 days = (C1 / C0)×100%.
[0145] The capacity recovery rate (%) of the lithium-ion battery after storage at 60°C for 90 days = (C2 / C0)×100%.
[0146] (5) High temperature storage experiment:
[0147] The battery was tested for 5 charge and discharge cycles at room temperature with a charge and discharge rate of 1C, and then charged to a fully charged state at a rate of 1C. The 1C capacity Q0 and battery volume V0 were recorded respectively. The fully charged battery was stored at 60°C for 90 days, and the battery volume V1 and 1C discharge capacity Q1 were recorded. The battery was then charged and discharged at a rate of 1C for 5 weeks at room temperature, and the 1C discharge capacity Q2 was recorded. The experimental data such as the battery's high-temperature storage capacity retention rate, capacity recovery rate, and volume change rate were calculated, and the recorded results are shown in the following table. The calculation formulas used are as follows: Capacity retention rate (%) = Q1 / Q0×100%; Capacity recovery rate (%) = Q2 / Q0×100%; Volume change rate (%) = (V1-V0) / V0×100%.
[0148] The test results are shown in Table 1.
[0149] Table 1
[0150]
[0151] It can be seen from Table 1 that the electrolyte of the embodiment has a low HF content during storage and has excellent stability. Applying the electrolyte additive composition of the present application to a battery can significantly improve the cycle performance of the battery and enhance the high voltage resistance of the electrolyte, thereby effectively improving the high temperature cycle performance and high temperature storage performance of the battery under high voltage, and extending the cycle life of the battery.
[0152] By comparing Example 1 with Comparative Examples 3 to 6, it can be seen that the additive containing only a single group cannot achieve the improvement of battery cycle performance as shown in Formula 1. It can be seen that the functional additive with the structural formula shown in Formula 1 in the present application is not the independent effect of a single functional group, but the whole structure produces a multi-faceted synergistic effect in the electrolyte, and this synergistic effect is the key to improving battery performance and stability.
[0153] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. An electrolyte additive composition, characterized in that: The electrolyte additive composition includes a lithium salt additive and a functional additive, and the structural formula of the functional additive is shown in Formula 1:
2. The electrolyte additive composition according to claim 1, characterized in that: The mass ratio of the lithium salt additive to the functional additive is (0.5-1): (0.3-1); Preferably, the lithium salt additive includes at least one of lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, lithium bis(oxalatoborate), and lithium difluorobis(oxalatophosphate).
3. The electrolyte additive composition according to claim 1, characterized in that: The electrolyte additive composition further includes a carbonate additive; the mass ratio of the carbonate additive to the functional additive is (0.2-1): (0.3-1); Preferably, the carbonate additive includes vinylene carbonate and / or fluoroethylene carbonate.
4. The electrolyte additive composition according to any one of claims 1 to 3, characterized in that: The electrolyte additive composition further includes a sulfur-containing additive; the mass ratio of the sulfur-containing additive to the functional additive is (0.5-2): (0.3-1); Preferably, the sulfur-containing additive includes at least one of propylene sulfite, 1,3-propane sultone, and ethylene sulfate.
5. An electrolyte, characterized in that: The electrolyte comprises a lithium salt, an organic solvent and the electrolyte additive composition according to any one of claims 1 to 4.
6. The electrolyte according to claim 5, characterized in that The mass fraction of the lithium salt in the electrolyte is 9.5% to 15%; and / or, The mass fraction of the organic solvent in the electrolyte is 80% to 90%; and / or, The mass fraction of the electrolyte additive composition in the electrolyte is 0.5% to 5%.
7. The electrolyte according to claim 5 or 6, characterized in that The mass fraction of the functional additive in the electrolyte is 0.3% to 1%; and / or, The mass fraction of the lithium salt additive in the electrolyte is 0.5% to 1%; and / or, The mass fraction of the carbonate additive in the electrolyte is 0.2-1%; and / or, The mass fraction of the sulfur-containing additive in the electrolyte is 0.5% to 2%.
8. The electrolyte according to claim 5 or 6, characterized in that The organic solvent comprises at least two of ethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate; Preferably, the organic solvent comprises ethylene carbonate and ethyl methyl carbonate; More preferably, the organic solvent further comprises at least one of dimethyl carbonate and diethyl carbonate.
9. A battery, characterized in that: The battery comprises the electrolyte according to any one of claims 5 to 8.
10. The battery according to claim 9, characterized in that The battery further comprises a negative electrode sheet containing a negative electrode active material; and / or, The battery also includes a positive electrode sheet containing a positive electrode active material; Preferably, the negative electrode active material includes a carbon-based negative electrode material; the positive electrode active material includes a nickel cobalt manganese ternary material, and the chemical formula of the nickel cobalt manganese ternary material is Li(Ni x Co y Mn z )O2, where 0.5 ≤ x < 0.8, 0 < y ≤ 0.3, 0 < z ≤ 0.3 and x + y + z = 1.
Citation Information
Patent Citations
Electrolyte additive composition, electrolyte, and secondary battery
CN113540569A
Anti-overcharge electrolyte and lithium battery
CN114464888A
Functional aliphatic and / or aromatic amine compounds or derivatives as electrolyte additives to reduce gas generation in li-ion batteries
US11018371B1
Antiviral agents
US20070287699A1
HIGH VOLTAGE ELECTROLYTE (Muldoon, Allred)
US20100209780A1